Impact of Leaf Traits on Temporal Dynamics of Transpired Oxygen Isotope Signatures and Its Impact on Atmospheric Vapor - Dubbert, Maren; Kübert, Angelika; Werner, Christiane (Frontiers in Plant Science, 2017)
Oxygen isotope signatures of transpiration (δE) are powerful tracers of water movement from plant to global scale. However, a mechanistic understanding of how leaf morphological/ physiological traits effect δE is missing. A laser spectrometer was coupled to a leaf-level gas-exchange system to measure fluxes and isotopic signatures of plant transpiration under controlled conditions in seven distinct species (Fagus sylvatica, Pinus sylvestris, Acacia longifolia, Quercus suber, Coffea arabica, Plantago lanceolata, Oxalis triangularis). We analyzed the role of stomatal conductance (gs) and leaf water content (W) on the temporal dynamics of δE following changes in relative humidity (rH). Changes in rH were applied from 60 to 30 % and from 30 to 60 %, which is probably more than covering the maximum step changes occurring under natural conditions. Further, the impact of gs and W on isotopic non-steady state Isofluxes was analyzed. Following changes in rH, temporal development of δE was well described by a one-pool modelling approach for most species. Isofluxes of δE were dominantly driven by stomatal control on E, particularly for the initial period of 30 min following a step change. Hence, the deviation of isofluxes from isotopic steady state can be large, even though plants transpire near to isotopic steady state. Notably, not only transpiration rate and stomatal conductance, but also the leaf traits stomatal density (as a measure of gmax) and leaf water content are significantly related to the time constant (τ) and non-steady-state isofluxes. This might provide an easy-to-access means of a priori assumptions for the impact of isotopic non-steady-state transpiration in various ecosystems. We discuss the implications of our results from leaf to ecosystem scale.